Genomic landscape of myelodysplastic/myeloproliferative neoplasm can predict response to hypomethylating agent therapy. Issue 8 (3rd July 2022) - Karantanos, Theodoros; Tsai, Hua-Ling; Gondek, Lukasz P.; DeZern, Amy E.; Ghiaur, Gabriel; Dalton, W. Brian; Gojo, Ivana; Prince, Gabrielle T.; Webster, Jonathan; Ambinder, Alexander; Smith, B. Douglas; Levis, Mark J.; et al.
Abstract: There are currently no known predictors of myelodysplastic syndrome (MDS)/myeloproliferative overlap neoplasm (MPN) patients' response to hypomethylating agents (HMA). Forty-three patients with MDS/MPN who were treated with HMA during chronic phase and had next-generation sequencing using the established 63-genes panel were identified. Complete and partial remission and marrow response were assessed based on the MDS/MPN International Working Group response criteria. On univariate analysis, younger age, higher number of mutations, and mutations in SETBP1, RUNX1, or EZH2 were associated with no response. Multivariable analysis for modeling response were conducted via least absolute shrinkage and selection operator logistic regression approach, and showed that mutations in SETBP1, RUNX1, or EZH2 predict lack of HMA response. While limited by sample size, our findings suggest that genomic landscape can potentially identify MDS/MPN patients with lower likelihood of response to HMA.